STUDY ON THE EFFECT OF BRAND EQUITY ON IPHONE PRODUCT CUSTOMERS IN SEMARANG CITY - Nadya Astarina Novera (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
In the growth of the world economy, business competition between companies is tight and increasing, especially in business competition in Indonesia. Many companies are competing to keep their customers in order to keep using the products offered. Every company tries to fulfill the wishes of consumers by delivering the desired goods or services (Halim & Iskandar, 2019). Technology companies are one of the companies that compete in developing their products. This study describes the influence of Perceived Quality, Brand Image, and Brand Experience on Customer Loyalty with Brand Equity as an intermediate variable to iPhone smartphone users in Semarang. The sample needed in this study is iPhone product users who have made purchases and used iPhone products at least 2 times from the type of iPhone product line. Keyword: Perceived Quality, Brand Image, Brand Experience, Brand Equity, Customer Loyalty